How do women's partners view perinatal mental health services? A qualitative meta‐synthesis. (30th August 2017) - Lever Taylor, Billie; Billings, Jo; Morant, Nicola; Johnson, Sonia
Abstract: Objectives: Perinatal mental health difficulties are prevalent among women and can adversely affect their partners too. There is also increasing recognition that a woman's partner can play a vital role in relation to her perinatal mental health and should be supported and involved in decisions about her care. Yet it is unclear how services are experienced by the partners of women with perinatal mental health difficulties. This study aimed to synthesize qualitative evidence of partners' views of perinatal mental health care. Methods: A systematic search of 5 electronic databases identified 20 studies that met the inclusion criteria. The findings of these studies were synthesized using an approach based on meta‐ethnography. Results: Six themes were identified, namely, the marginalization and neglect of women's partners, an unmet need for information, partners' ambivalence about involvement and support, practical barriers to involvement, views about support for women's partners, and the impact on partners of the care women received. Conclusions: Given the importance of women's partners in relation to perinatal mental health as well as to women's engagement with support and treatment outcomes, greater consideration should be given to their needs to ensure they feel well informed and involved in perinatal mental health care, rather than marginalized. However, professionals also need to challenge the barriers to involvement and support that women's partners face and consider the ways in which services may reinforce these barriers.